A lakóparkok és lakóparkszerű létesítmények általános jellemzői a magyarországi megyei jogú városokban - Hegedűs, Gábor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The modern gated communities first appeared in East-Central Europe after the collapse of state socialist systems. Moving into gated communities turned into one characteristic form of residential segregation. Since the beginning of the 1990s gated communities (in Hungarian: lakópark, 'residential park') began to be built in Budapest and in its direct suburban gravitation zone in Hungary. The largest cities in Hungary have a special administra-tive status (City with County Rights). We analyzed residential parks and residential park-like developments in the so-called Cities with County Rights having mostly over 50 thousands inhabitants. We typified residential parks, analyzed their geographical dispersion in the category mentioned above. We can observe significant differences in the numbers and spatial distribution of residential parks amongst the analyzed cities.